Measurement of underlying event characteristics using charged particles in pp collisions at √s=900GeV and 7 TeV with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acharya, B; et al. (2011)
Measurements of charged particle distributions, sensitive to the underlying event, have been performed with the ATLAS detector at the LHC. The measurements are based on data collected using a minimum-bias trigger to select proton-proton collisions at center-of-mass energies of 900 GeV and 7 TeV. The "underlying event" is defined as those aspects of a hadronic interaction attributed not to the hard scattering process, but rather to the accompanying interactions of the rest of the proton. Three regions are defined in azimuthal angle with respect to the highest transverse momentum charged particle in the event, such that the region transverse to the dominant momentum-flow is most sensitive to the underlying event. In each of these regions, distributions of the charged particle multiplicity, transverse momentum density, and average pT are measured. The data show generally higher underlying event activity than that predicted by Monte Carlo models tuned to pre-LHC data. © 2011 American Physical Society.